(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Strict adherence to aseptic technical procedures and CVC care is the top priority in preventing CLABSI and other complications associated with CVC use. The study aims to assess the compliance of nurses in the emergency and intensive care units at the Central Geriatric Hospital with CVC care protocols. Method: A cross-sectional descriptive study was conducted on nurses performing CVC care in the emergency and intensive care units at the Central Geriatric Hospital from January 2025 to December 2025. Results: The study involved 66 nurses with 132 CVC care instances, with females accounting for 71.2%. The most common age group was 30–40 years old, representing 69.7%, with 81.8% holding college degrees and having 5–10 years of work experience at 60.61%. Most nurses possessed knowledge about CVC care, with 46.97% understanding the key steps and 37.88% knowing the entire procedure. The overall compliance rate with the CVC care process is relatively low at 36.4%. The compliance rate for both observations is 13.6%, which is lower than the 42.4% for one observation and 43.9% for no observations. Among the steps performed, those related to distal catheter care have relatively low rates of 53.8% and 44.7%, respectively. The important steps in the process are highly adhered to, with compliance rates above 75%. Conclusion: The compliance rate with the CVC care process is relatively low at only 36.4%, with an average score of 21.03 ± 1.58 points. The pre- and post-care steps generally follow the process, except for the distal catheter care steps.